(SFSLVXJOJ MAL XF[PRNRDLA X]P YNLM]Ps - Callister William D ((SXilrnga(Sw(B,s, 2008)
(SFLVAD]DJ AXROLMJ EROJ MAL EFVORL OFXAQY AXRO]P J EROJ X]P MUYVXANNLM]P VXFUF]P AXFNFLFV X]P VXFUF]P ELA[YVJ OJ[APLMFV LELRXJXFV ELAXAUA[FV MAL OJ[APLVORL LV[YURSRLJVJV AVXR[LA X]P YNLM]Ps
(SFLVAD]DJ AXROLMJ EROJ MAL EFVORL OFXAQY AXRO]P J EROJ X]P MUYVXANNLM]P VXFUF]P AXFNFLFV X]P VXFUF]P ELA[YVJ OJ[APLMFV LELRXJXFV ELAXAUA[FV MAL OJ[APLVORL LV[YURSRLJVJV AVXR[LA X]P YNLM]Ps